Pengaruh Pemberian Zat Pengatur Tumbuh Hormon Auksin dan Sitokinin Terhadap Pertumbuhan Tunas dan Akar Zaitun (Olea europaea) Menggunakan Metode Microcutting - Paramitha, Armanda Bella; Achyar, Zhahrotun Khofifah Nur; Azizi, Rosita Imro’atul; Jayanti, Gatra Ervi; Ramadhan, Majida; Prasetyowati, Eka (Biopedagogia, 2025)
Olive plants (Olea europaea) are widely used as traditional medicine and have high economic value, but olive cultivation in Indonesia still faces many challenges. This study aims to evaluate the effect of providing plant growth regulators (ZPT) auxin and cytokinin hormones on the growth of olive shoots and roots using the microcutting method. The study was conducted at the Orchidology Laboratory, Islamic University of Malang with an experimental method of three treatments, namely water control, Biogen, and Bregadium. The parameters observed included the number and quality of shoot and root growth. The results showed that Biogen and Bregadium were able to accelerate the emergence of shoots on the 3rd day, while the control grew on the 10th day. Observations of root growth showed that Bregadium was able to stimulate root formation in more samples even though the quality was still very thin and few. In contrast, Biogen only produced one thin root in one sample. The conclusion of the study states that the combination of Bregadium ZPT hormones has the potential to be more effective in stimulating the growth of olive roots and shoots vegetatively. This study recommends optimizing the concentration and frequency of ZPT application for more optimal growth results.